Law Enforcement of Violent Theft in Indonesia: Analysis of Decision 201/Pid.B/2024/PN Ktg - Dino Dwi Aristo; Yoyok Ucuk Suyono; Dudik Djaja Sidarta; subekti Subekti; Hartoyo Hartoyo (CV. AFDIFAL MAJU BERKAH, 2026)
Robbery constitutes a serious criminal offense in the Indonesian criminal justice system because it combines the unlawful appropriation of property with the use or threat of violence against victims. Although Article 365 of the Indonesian Criminal Code provides a legal framework for regulating violent theft, judicial practice often encounters interpretative challenges regarding the elements of violence, aggravating circumstances, and sentencing proportionality. This study aims to analyze the legal construction of robbery under Article 365 of the Criminal Code, examine the judicial reasoning (ratio decidendi) in Decision Number 201/Pid.B/2024/PN Ktg, and evaluate the decision’s consistency with the principles of criminal liability, proportional punishment, and legal certainty. The research employs a qualitative normative legal method using statutory, case-based, conceptual, and analytical approaches by examining primary legal materials such as the Criminal Code, the Criminal Procedure Code, and the relevant court decision, supported by secondary and tertiary legal sources. The findings indicate that the court systematically assessed the relationship between factual evidence and statutory elements of the offense and confirmed the fulfillment of both actus reus and mens rea in establishing criminal liability. The judgment also reflects the application of the proportionality principle in sentencing. However, interpretative discretion regarding violence and aggravating circumstances may lead to inconsistencies in judicial decisions. Therefore, this study recommends strengthening judicial interpretation guidelines and developing an integrated judgment database to enhance doctrinal consistency, legal certainty, and transparency in criminal law enforcement in Indonesia.